STUDI BIBLIKAL KONSEP PELAYAN KRISTEN BERDASARKAN 2 TIMOTIUS 1 : 3 -18 - Yonatan Alex Arifianto; Priyantori Widodo (Alucio Dei, 2021)
The service that is done by the servants has many obstacles, because there is no responsibility and integrity in serving so that everything that is done in serving does not have the firmness of faith. Using descriptive qualitative methods with a literature study approach aims that services must have the qualifications contained in the context of 2 Timothy 1: 3-18. It can be concluded that the concept of Christian ministry based on 2 Timothy 1: 3-18 is that the servant first believes in the call to be a servant (2 Timothy 1:11). The call to the servant becomes the basis for someone to serve. Second, it opens the paradigm that service is a gift from God (2 Tim.1: 9). Third, a servant who stirs up gifts (2 Tim.1: 6). The fourth is a servant who keeps a beautiful treasure (2 Tim.1: 14). And the last one is the servant who has faith (2 Tim.1: 5-6). And these qualifications are the basis for placing ministry in the context of 2 Timothy 1: 3-18, for believers today to continue serving God.